2021
DOI: 10.1111/and.13991
|View full text |Cite
|
Sign up to set email alerts
|

Sperm binding to hyaluronan is an excellent predictor of Nili‐Ravi buffalo bull fertility

Abstract: This study reports the first evaluation of sperm hyaluronan binding assay (HBA) for predicting the fertility of Nili‐Ravi buffalo bulls in relation to standard parameters of sperm quality. Cryopreserved semen doses of low (n = 6), medium (n = 3) and high fertility (n = 8) bulls based on their respective return rates were used. Significantly, more spermatozoa bound to hyaluronan from the most fertile bulls (57.15% ± 1.44) compared with medium (42.46% ± 1.08) and low fertility bulls (29.70% ± 0.78). A strongly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Frozen-thawed camel spermatozoa showed significantly less binding than fresh spermatozoa (3 to 24 %), and also less binding than frozen-thawed Nili-Ravi buffalo spermatozoa (27 to 57%; Awan et al 2021). Low post-thaw binding was expected since dromedary camel spermatozoa do not tolerate freezing-thawing procedure well (Morton et al 2010).…”
Section: Proakap4 Correlationsmentioning
confidence: 89%
See 2 more Smart Citations
“…Frozen-thawed camel spermatozoa showed significantly less binding than fresh spermatozoa (3 to 24 %), and also less binding than frozen-thawed Nili-Ravi buffalo spermatozoa (27 to 57%; Awan et al 2021). Low post-thaw binding was expected since dromedary camel spermatozoa do not tolerate freezing-thawing procedure well (Morton et al 2010).…”
Section: Proakap4 Correlationsmentioning
confidence: 89%
“…Some potential for assessing stallion sperm fertility was reported as the spermatozoa bound to HBA, but the test failed to predict the success of AI (Colleoni et al 2011). A study on Nili-Ravi buffalo bull fertility reported high prediction value for HBA test (predicting 67.9% variability) from frozen-thawed sperm samples (Awan et al 2021).…”
Section: Sperm-hyaluronan Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…[ [160][161][162][163]167,201] Hyaluronan-rich medium: A droplet of medium with sperm is put in contact with a droplet of medium with hyaluronic acid. Sperm in the interface of the droplets are selected.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronic acid-binding proteins have been identified in sperm of various species [159]. And in some, such as in buffalo, sperm binding to hyaluronic acid has been correlated with fertility after AI [160]. A plethora of studies in humans has shown that sperm that bind hyaluronic acid have better quality parameters.…”
Section: Sperm Interaction With Oviductal Fluidmentioning
confidence: 99%